2013
DOI: 10.3109/08958378.2013.765932
|View full text |Cite
|
Sign up to set email alerts
|

Airway inflammatory responses to diesel exhaust in allergic rhinitics

Abstract: DE, at a dose previously shown to cause neutrophilic inflammation in healthy individuals, induced no neutrophilic inflammation in the lower airways of allergic rhinitics, consistent with previous reports in asthmatics. Although there was no increase in allergic inflammatory cell numbers, the reduction in tryptase in the epithelium may indicate mast cell degranulation. However, this occurred in the absence of allergic symptoms. These data do not provide a simplistic explanation of the sensitivity in rhinitics t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 43 publications
1
17
0
1
Order By: Relevance
“…MPO, produced by neutrophils, serves as a surrogate marker for this inflammation [19]. Previous reports have shown that DE can increase neutrophil counts and MPO concentration in bronchial samples [41,43]. The concentration of MPO is also responsive to allergen; MPO increases in BWs from asthmatics after segmental allergen [44], and in NLF after nasal challenge in patients with allergic rhinitis [45].…”
Section: Discussionmentioning
confidence: 99%
“…MPO, produced by neutrophils, serves as a surrogate marker for this inflammation [19]. Previous reports have shown that DE can increase neutrophil counts and MPO concentration in bronchial samples [41,43]. The concentration of MPO is also responsive to allergen; MPO increases in BWs from asthmatics after segmental allergen [44], and in NLF after nasal challenge in patients with allergic rhinitis [45].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of NAEB varied from country to country, it was hard to provide a convincing explanation for the high prevalence of NAEB in our study. It is possible that the high air pollution in Guangzhou could be a factor contributing to the high prevalence of NAEB in our study because air pollution has been shown to have an effect on airway inflammation . However, because we did not measure exposure or air pollution, this is only a speculation.…”
Section: Discussionmentioning
confidence: 90%
“…It is possible that the high air pollution in Guangzhou could be a factor contributing to the high prevalence of NAEB in our study because air pollution has been shown to have an effect on airway inflammation. [28][29][30] However, because we did not measure exposure or air pollution, this is only a speculation.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported associations between short-term exposure to air pollution and acute changes in inflammatory markers, such as increase in pulmonary interleukin (IL-6) measured in exhaled breath condensate (Behndig et al 2006;Kongerud et al 2006;Thompson et al 2010), as well as systemic IL-6 and TNFa levels in adult populations (Tsai et al 2012), including subgroups with preexisting chronic inflammatory conditions (Rückerl et al 2007). However, others failed to demonstrate associations with IL-6 (Bräuner et al 2008;Panasevich et al 2009;Zuurbier et al 2011) or TNF-a (Bräuner et al 2008;Larsson et al 2013). Studies of long-term exposure to air pollution demonstrate mixed effects on blood markers of systemic inflammation (Chuang et al 2011;Forbes et al 2009;Mostafavi et al 2015;Panasevich et al 2009).…”
Section: Introductionmentioning
confidence: 99%